2005
DOI: 10.1051/parasite/2005121003
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of protective immunity induced againstSchistosoma mansonivia DNA priming with the large subunit of calpain (Sm-p80) in the presence of genetic adjuvants

Abstract: Summary :Despite advances in control via snail eradication and large-scale chemotherapy using praziquental, schistosomiasis continues to spread to new geographic areas particularly in sub-Saharan Africa. Presently, there is no vaccine for controlling this disease. We have concentrated on a functionally important schistosome antigen Sm-p80 as a possible vaccine candidate for schistosomiasis. Here we report the proliferation of spleen cells in response to the recombinant Sm-p80 protein and cytokine (IFN-γ and IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 15 publications
8
46
0
Order By: Relevance
“…More than 100 such antigens have been identified, about 15% of which confer protection of varying degrees and are considered promising though they do not quite reach the level of immunity elicited following vaccination with irradiated cercariae (Bergquist et al 2002;Hewitson et al 2005). In some cases, cDNA clones encoding protective epitopes have been characterized, and the identities of several partially protective antigens are known, including paramyosin (Gobert and McManus 2005), glutathione S-transferase (Capron et al 2005), triose phosphate isomerase (TPI; Harn et al 1992), 14 kDa fatty acid binding protein (Fonseca et al 2006), Sm23 (Da'dara et al 2001Da'dara et al 2002), GAPDH (Argiro et al 2000), and Sm-p80 (Siddiqui et al 2003a;Siddiqui et al 2003b;Siddiqui et al 2005a;Siddiqui et al 2005b). Vaccinations with synthetic or recombinant schistosomal antigens representing selected epitopes have induced partial protection and/or reduced female fecundity in animal models (Balloul et al 1987;Osburn and Stott 1989;Boulanger et al 1991a;Soisson et al 1992;Lebens et al 2003;Tallima et al 2003;Veprek et al 2004).…”
Section: Vaccine Candidatesmentioning
confidence: 97%
See 1 more Smart Citation
“…More than 100 such antigens have been identified, about 15% of which confer protection of varying degrees and are considered promising though they do not quite reach the level of immunity elicited following vaccination with irradiated cercariae (Bergquist et al 2002;Hewitson et al 2005). In some cases, cDNA clones encoding protective epitopes have been characterized, and the identities of several partially protective antigens are known, including paramyosin (Gobert and McManus 2005), glutathione S-transferase (Capron et al 2005), triose phosphate isomerase (TPI; Harn et al 1992), 14 kDa fatty acid binding protein (Fonseca et al 2006), Sm23 (Da'dara et al 2001Da'dara et al 2002), GAPDH (Argiro et al 2000), and Sm-p80 (Siddiqui et al 2003a;Siddiqui et al 2003b;Siddiqui et al 2005a;Siddiqui et al 2005b). Vaccinations with synthetic or recombinant schistosomal antigens representing selected epitopes have induced partial protection and/or reduced female fecundity in animal models (Balloul et al 1987;Osburn and Stott 1989;Boulanger et al 1991a;Soisson et al 1992;Lebens et al 2003;Tallima et al 2003;Veprek et al 2004).…”
Section: Vaccine Candidatesmentioning
confidence: 97%
“…The protein has been shown to be exposed at the host parasite interface (Siddiqui et al 1993;Braschi and Wilson 2006) and to be naturally immunogenic (HotaMitchel et al 1999). While the natural immunogenicity of the molecule does not provide protection under conditions of natural infection, it has been demonstrated that it is possible to present calpain to the immune system in such a way as to induce potent immunity in experimental animals (Siddiqui et al 2003a;Siddiqui et al 2003b;Siddiqui et al 2005a;Siddiqui et al 2005b). Another functionally relevant vaccine candidate is a sugar-transporting protein designated SGTP4 (Skelly and Shoemaker 1996;Jiang et al 1996).…”
Section: In Search Of Functionally Important Vaccine Candidatesmentioning
confidence: 98%
“…At present, to our knowledge, Sm-p80 is the sole schistosome vaccine candidate that has been tested for its prophylactic, antifecundity and therapeutic efficacy in different vaccine formulations and approaches (e.g., naked DNA alone; recombinant protein with adjuvants; and prime with DNA, followed by boosting with protein plus adjuvants) in two experimental animal models (mouse and baboon) of infection and disease. 16,[50][51][52][53][54][55][56][57][58][59][60][61][62] Furthermore, the validity of Sm-p80 as a viable vaccine candidate has been reinforced by the work of five "research groups" who have independently demonstrated reproducible and consistent protective efficacy in mice following challenge infection using calpain or its peptides as an antigen (Nagoya City University Medical School, Nagoya, Japan; 63 [50][51][52][53][54][55][56][57][58][59][60][61][62] ). Sm-p80-based vaccine formulations have three protective effects: worm reduction, antifecundity effect and protection against acute schistosomiasis.…”
Section: Discussionmentioning
confidence: 99%
“…The strategy commonly used to increase the immune response induced by antigen-encoded DNA vaccines is to add in the vaccine formulation cytokines-encoded plasmids. The genetic adjuvant IL-12 has been showed to increase splenocyte proliferation and protection in mice vaccinated with the large subunit of calpain (Siddiqui et al 2005). However, the use of IL-12 as a genetic adjuvant to Sm14 DNA vaccine failed to enhancer protection against challenge infection in mice (Fonseca et al 2006).…”
Section: Assessment Of Humoral Immune Response Elicited By Pecl -Sea-mentioning
confidence: 99%